?ANATOLIONE: A NEW DITERPENE FROM MARRUBIUM PARVIFLORUMOLIGODON - BAL, YII.DIZ; KABAN, SFNIZ; NIZAMI, S.S. (Biological Sciences - PJSIR, 1995)
Chemical constituents of Marrubium parviflorum have been investigated. Thus a new diicrpcncic compoud has been isolated and its structure is elucidated on the basis or spectral studies which shows it is hitherto an unreported ditcrpcnc.